2019
DOI: 10.25046/aj040439
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Bodily Movements of the Visually Impaired Children by Airflow

Abstract: This study involved three departments of teachers and students. The concept of the flowmotivated exercise implemented with a set of flow nozzles. A computer-controlled airflow with specific music introduced, and the motion responses from the participants were analyzed during the initial test and field study. During the initial examination, we adjusted the magnitude and distance setting of the flow and allowed the children to grab the air without music. Structural design, magnetic valve, and interface were impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous studies have also shown positive effects through airflow [6] and tactile sensations [7] in promoting children's physical activity. Baker et al developed a 'ring' to be worn by an orchestral conductor and a 'vibration matrix' through a twodimension haptic signal through which the conductor could convey their intent to a visually impaired musician [8].…”
Section: Haptic Devices and Teachmentioning
confidence: 99%
“…Previous studies have also shown positive effects through airflow [6] and tactile sensations [7] in promoting children's physical activity. Baker et al developed a 'ring' to be worn by an orchestral conductor and a 'vibration matrix' through a twodimension haptic signal through which the conductor could convey their intent to a visually impaired musician [8].…”
Section: Haptic Devices and Teachmentioning
confidence: 99%
“…Several study are done on the practice of physical activities for different categories people. For example, [19] used the airflow to reinforce the motivation and the bodily movements for children who are visually impaired to increase positive interactions. In [20] the Microsoft Kinect V1 is used in a yoga exergaming dedicate for blind and low vision people.…”
Section: Introductionmentioning
confidence: 99%